Persepsi Stakeholders In Judgemnt Mahasiswa Akuntansi Universitas Nusa Cendana Terhadap Pencegahan Fraud Dalam Layanan Pendidikan - Athiyyah Maisaan Ms; Maria Prudensiana Leda Muga; Yohanes Demu (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to determine whether fraud in academic education is a problem that can disrupt the integrity and quality of higher education. Therefore, effective prevention efforts are needed through strengthening the perception and ethical assessment of students as stakeholders in judgment. This study aims to analyze the influence of student perceptions of stakeholders in judgment on fraud prevention in academic education. This study uses a quantitative approach with a survey method of 55 students of Nusa Cendana University. Data were collected through questionnaires and analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, simple linear regression analysis, t-tests, and coefficients of determination. The results show that student perceptions of stakeholders in judgment have a positive and significant effect on academic fraud prevention. The coefficient of determination (R Square) value of 0.504 indicates that student perceptions are able to explain 50.4% of the variation in fraud prevention. This study emphasizes the importance of strengthening academic ethics and integrity as a fraud prevention strategy in the higher education environment).